Antinociceptive activity of Boesenbergia rotunda (L.) Mansf. hexane extract and its mechanisms of actions in mice - Makhtar, Nor'adilah (2014)
Boesenbergia rotunda, fingerroot or locally known as "temu kunci" is commonly used in Southeast Asia as food ingredient and folk medicine for relieving pain related to the stomach, abdomen, joint, and muscle. Currently, there is lack of studies on the analgesic properties of the plant. Hence this study is an attempt to investigate the antinociceptive activity of the Boesenbergia rotunda hexane extract (BRHE) using various models of chemicals- and thermal-induced nociception in mice and thus promote and support the analgesic claim of B. rotunda. Results from the antinociceptive study showed that oral administration of BRHE produced significant (p<O.OS) inhibition of mice writhing response with the highest dose of 300 mg/kg resulting in 82.19% inhibition. Results from the hot plate test also showed that BRHE produced significant (p<0.05) increase in the latency time compared to control groups. Additionally, in the formalin test, the nociceptive activity was inhibited significantly (p<0.05) at both phases by BHRE with the highest dose 300 mg/kg resulting in 67.7% inhibition of the first phase and 85.9% inhibition of the second phase. Oral administration of BRHE also significantly (p<0.05) reduced nociceptive activity caused by capsaicin and glutamate with the highest dose 300 mg/kg causing inhibition of 92.3% and 92% respectively. Pretreatment of tJ1e mice with naloxone (non-selective opioid antagonist), beta-funaltrexamine (mu opioid receptor antagonist), norbinaltorphimine (kappa opioid receptor antagonist), L-arginine (kappa opioid receptor antagonist), tetraethylammonium (non-selective voltagedependent K+ channel blocker), and charybdotoxin (large conductance Ca2+ activated K+ channel blocker) at designated doses significantly (p<0.05) reversed BRHE-induced antinociception (300 mg/kg) in the acetic acid-induced writhing test. Together, these results suggested that BRI-IE may exe11 its antinociceptive activity through activation of mu opioid receptor and kappa opioid receptor. It also indicates that BRHE-induced antinociception was possibly related to its ability to inhibit the L-arginine/nitric oxide pathway, together with the activation of voltage-dependent Kt channel and Ca2+ activated K+ channel. In addition, no signs of toxicity or mortality were observed in the preliminary acute toxicity test. Furthermore, no significant alteration of mice motor performance in rota-rod test was exhibited, ruling out the sedative effect of BRHE. The antinociceptive action demonstrated in the present study supports, at least in part, the ethnomedical uses of this plant.